Design of antibody-functionalized carbon nanotubes filled with radioactivable metals towards a targeted anticancer therapy. Issue 25 (6th January 2016) - Spinato, Cinzia; Perez Ruiz de Garibay, Aritz; Kierkowicz, Magdalena; Pach, Elzbieta; Martincic, Markus; Klippstein, Rebecca; Bourgognon, Maxime; Wang, Julie Tzu-Wen; Ménard-Moyon, Cécilia; Al-Jamal, Khuloud T.; Ballesteros, Belén; Tobias, Gerard; et al.
Abstract : SWCNTs filled with radioactivable metal halides have been covalently functionalized with an antibody targeting the epidermal growth factor receptor. Abstract : In the present work we have devised the synthesis of a novel promising carbon nanotube carrier for the targeted delivery of radioactivity, through a combination of endohedral and exohedral functionalization. Steam-purified single-walled carbon nanotubes (SWCNTs) have been initially filled with radioactive analogues ( i.e. metal halides) and sealed by high temperature treatment, affording closed-ended CNTs with the filling material confined in the inner cavity. The external functionalization of these filled CNTs was then achieved by nitrene cycloaddition and followed by the derivatization with a monoclonal antibody (Cetuximab) targeting the epidermal growth factor receptor (EGFR), overexpressed by several cancer cells. The targeting efficiency of the so-obtained conjugate was evaluated by immunostaining with a secondary antibody and by incubation of the CNTs with EGFR positive cells (U87-EGFR+), followed by flow cytometry, confocal microscopy or elemental analyses. We demonstrated that our filled and functionalized CNTs can internalize more efficiently in EGFR positive cancer cells.